Effectiveness of Si Pathol Media Based on Articulate Storyline 3 for Learning Outcomes of Science Elementary School Students - Irsyad, Fuad; Su' ad; Khamdun (Asian Journal of Assessment in Teaching and Learning, 2023)
This research aims to enhance the learning outcomes of sixth-grade science subjects using Si Pathol media. It is a Research and Development (R&D) study focused on product development through planning, production, and evaluation of product validity. The development process consists of eight steps. Data analysis techniques include validation sheet analysis, feasibility questionnaire analysis, teacher and student response questionnaires, and t-test analysis to determine the effectiveness of the developed learning media. The effectiveness data of Si Pathol, based on the Articulate Storyline 3 application for science subjects, were analyzed using gain tests and t-tests at a significance level of 0.05. The product trial design used a pretest-posttest control group design, with Class VI students from SD Negeri 1 Karangmangu as the experimental group and students from SD Negeri Temperak as the control group. The results showed that Si Pathol learning media effectively improved learning outcomes. The average pretest scores for the experimental and control classes were 58.95 and 61.12, respectively. After the intervention, the posttest averages increased to 87.34 and 87.80. The t-test results indicated a significant difference, with t = 3.933 and a significance level of 0.000 < α = 0.05. In conclusion, the Si Pathol learning media based on the Articulate Storyline 3 application is proven to be appropriate, feasible, and effective for sixth-grade science learning. It is recommended that teachers use the Si Pathol learning media to improve student learning outcomes.